Ragam Seni Pertunjukan Jalanan Awal Abad XX - Salfia Rahmawati (Manuskripta, 2022)
Data collection on the variety of street performing arts is important as a marker of the diversity of cultural arts as well as showing the diversity of the people who interacted at that time. This paper shows a record of data written and illustrated in the manuscript of the National Library's collection coded KBG 940. The data represents at least two periods, namely the period before the manuscript was written in 1929 (although some of it might not anymore existed) and the time when the manuscript was written (although some of it might not anymore existed when the manuscript is read and studied currently). Based on the list, descriptions, and illustrations depicted, the data reflects the plurality of the socio-cultural life of the community moving dynamically as a representation of the cultural intersection of the community. Javanese, Chinese, Indian, Arabic, and Betawi in Yogyakarta. --- Pendataan mengenai ragam seni pertunjukan jalanan menjadi hal yang penting sebagai penanda keberagaman seni budaya sekaligus menunjukkan kemajemukan masyarakat yang berinteraksi pada masa tersebut. Tulisan ini menunjukkan sebuah catatan dan pendataan seni pertunjukan yang terekam dalam naskah koleksi Perpustakaan Nasional berkode KBG 940. Variasi seni pertunjukan yang berhasil didata setidaknya merepresentasikan dua masa, yaitu masa sebelum naskah ditulis tahun 1929 (meskipun sebagian telah hilang saat naskah ditulis) dan masa saat naskah ditulis (meskipun bisa jadi sebagian telah hilang saat naskah dibaca dan dikaji di masa sekarang). Dilihat dari daftar, keterangan, serta ilustrasi yang digambarkan, data yang ditampilkan menjadi cerminan kemajemukan kehidupan sosial budaya masyarakat bergerak dengan dinamis sebagai representasi persinggungan budaya dari komunitas Jawa, Cina, India, Arab, dan Betawi yang ada di Yogyakarta.